Above – The Sky of Varkaus - Itkonen, Matti (European Journal of Language and Literature, 2025)
The figurative fabric of being can be embroidered with words, images, ideas and fantasies. After all, we find this embroidery in the reality of language. In English we see the idea in such words as ‘coloured’, ‘mottled’, ‘pied’, ‘diversity’, ‘multiplicity’, for example, all of which correspond to the Finnish word ‘kirjo’, used in describing, among others, a rainbow trout, a harbour seal and the magical artefact in the national epic Kalevala. Medicines described in English as ‘broad-spectrum’, i.e. effective against many things, micro-organisms, have a ‘broad embroidery’ in Finnish. What is the meaning of a time of ‘embroidered culture’, of cultural multiplicity, and what is it like? Multi-face man inhabits the age of cultural multiplicity. Just as one-look man does. They can also be different sides of the same person. In fact, to counteract or provide an inverse existential partner for multi-face man, one-look man must be created and brought into the world. Through these existential opposites, it is possible to achieve sufficient depth and dimensionality for examining things. Multi-face man is born from the sphere of inwardness; its starting point is always at the core of existential interiority. One-look man in contrast exists purely as an externality – a being guided and led by an external will. Multi-face man, on the other hand, contains elements beyond the reach and control of external will: his interiority makes him an existential mystery. One-look man has a rote-learned fashionableness. There is nothing surprising about him since the known past also makes the future known and predictable in advance. All that remains is the repetition of the once learned. In short, multi-face man is the independent subject of his own life. One-look man is the non-independent subject of his existence because his externality – devoid of self-illumination – reflects the will of an external interiority.